Morfologija mešanic PP/PS, kompatibiliziranih z blokkopolimerom SBS - Radonjič, Gregor (Kovine zlitine tehnologije, 1998)
Morphological properties of immiscible blends of polypropylene (PP) and polystyrene (PS) with poly(styrene-b-butadiene-b-styrene) (SBS) block copolymer as a compatibilizer were studied by transmission electron microscopy(TEM) and wide angle X-ray diffraction (WAXD). TEM analysis revealed that in PP matrix dispersed aggregated PS particles are joined together with SBS shells. SBS also improves the adhesion between matrix and dispersed phase. addition of SBS to pure PP, or to PP/PS blends, changes degree of crystallinity, crystallite size and orientation systematically, indicating an obvious influence of SBS on PP crystallization behavior.
Keywords: kopolimeri; kompatibilnost; morfologija; karakterizacija; polipropilen; polistiren